1992
DOI: 10.1128/jvi.66.1.596-599.1992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a unique retrovirus associated with a fish tumor

Abstract: The walleye dermal sarcoma is a mesenchymal tumor which seasonally affects up to 27 % of adult walleye fish (Stizostedion vitreum). It arises multicentrically in the dermis, in which its development remains restricted. We report the molecular cloning of a type C retrovirus from this tumor. The genome of this virus (13.2 kb) is larger than that of all retroviruses and in that respect is approximated only by the recently characterized spumaviruses. In tumors, the predominantly unintegrated linear viral DNA has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…Cell-free filtrates of spring and fall tumors were analy/ed for the presence of WDSV RNA. Consistent with previous studies, a full-length (12-kilobase) viral genomic transcript was readily visualized in the spring tumor sample by northern blot analysis (Martineau et al 1992), but it was not demonstrable in the fall tumor inoculum (Figure I) from walleye discrete epidermal hyperplasia or to normal walleye skin RNA was observed, supporting the exogenous nature of WDSV.…”
Section: Rna Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Cell-free filtrates of spring and fall tumors were analy/ed for the presence of WDSV RNA. Consistent with previous studies, a full-length (12-kilobase) viral genomic transcript was readily visualized in the spring tumor sample by northern blot analysis (Martineau et al 1992), but it was not demonstrable in the fall tumor inoculum (Figure I) from walleye discrete epidermal hyperplasia or to normal walleye skin RNA was observed, supporting the exogenous nature of WDSV.…”
Section: Rna Analysissupporting
confidence: 89%
“…Analysis of total RNA from independent fall tumors showed that only low levels of a subgenomic WDSV transcript were found. The presence of this viral message, which likely encodes an accessory gene (Martineau et al 1992), could be an integral component of the mechanism for WDS induction.…”
Section: Rna Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Dermal sarcoma in walleye (Sander vitreus) is etiologically associated with the complex retrovirus, walleye dermal sarcoma virus (WDSV) (Martineau et al, 1992;Martineau et al, 1991;Walker, 1969;Yamamoto, Kelly, and Nielsen, 1985;Yamamoto et al, 1976). Walleye dermal sarcoma (WDS) is exceptional in its seasonal nature.…”
Section: Introductionmentioning
confidence: 99%
“…Retrovirus particles have been observed by Walker (1961) and later by Yamamoto et al (1985b) in walleye tumors. Walleye dermal sarcoma virus (WDSV) genome has been cloned directly from tumors and sequenced, showing that it is a complex retrovirus (Martineau et al 1991(Martineau et al , 1992Holzschu et al 1995). Virions of WDSV have been observed by electron microscopy, and the genome has been detected by in situ hybridization in tumors at high levels when collected in the spring (Poulet et al 1995).…”
Section: Walleye Dermal Sarcomamentioning
confidence: 99%